Do common dopaminergic variants modulate processing speed in cognitive aging? A longitudinal candidate gene study - Monica Anona Rose; Andrew C. Robinson; Antony Payton (PLoS ONE, 2026)
Amid a global shift toward older populations, understanding the mechanisms of cognitive aging is a public health priority. Processing speed shows age-related decline and predicts dementia risk. Neuroimaging links dopaminergic system integrity to cognitive performance in aging, but the contribution of common genetic variation remains unclear. This study tested whether common dopaminergic variants influence 12-year processing speed decline, performance at age 70, and other cognitive domains, with exploratory analyses of post-mortem pathology. A total of 89 linkage disequilibrium-independent variants (derived from 957 SNPs) across nine dopamine pathway genes ( TH , DDC , DRD1-3 , SLC6A3 , COMT , DBH , PPP1R1B ) were analysed in 1,539 participants from The University of Manchester Longitudinal Study of Cognition in Normal Healthy Old Age. Across single-variant, gene-based, and unweighted pathway allele score analyses, no associations survived multiple testing correction (Bonferroni p < 5.62 × 10⁻ 4 ). For processing speed decline, the strongest nominal signals were DRD2 rs10789943 (p = 0.0066) and DBH rs2005663 (p = 0.0074), followed by DRD2 rs12805897 (p = 0.013). For performance at age 70, the leading signal was DRD2 rs11214607 (p = 0.0025). Gene-based tests were non-significant (strongest: DRD2 for slopes p = 0.063; DRD2 for intercepts p = 0.019), and the dopamine pathway allele score was unassociated with decline (β = 0.001, p = 0.969) and performance (β = 0.009, p = 0.721). Null findings extended to fluid reasoning, episodic memory, and vocabulary, and to post-mortem analyses (neuropathology n = 116; synaptic density n = 50), including SNP-marker and marker-trajectory tests. With 80% power to detect single variants explaining at least 1.19% of variance and allele score effects explaining at least 0.51% of variance, no moderate-to-large effects of common dopaminergic variation on cognitive aging trajectories were detected. Smaller effects, or mechanisms not captured by common variant analyses such as rare variants, epigenetic regulation, or gene-environment interactions, may contribute to individual differences in cognitive aging.